Prediction of access failures - Deepa Narayan (2008)
Low vascular access blood flow is associated with an increased risk of thrombosis. A newly developed ultrasonic device (Transonic Demodialysis Monitor) (Manufactured by Transonic Systems Inc., Ithaca, New York, USA) that measures access flow and recirculation based on the Fick – principle of dilution has gained widespread clinical acceptance recently.